MEMPROGRAMKAN AKSES PEMBIAYAAN SYARIAH BAGI USAHA MIKRO KECIL DAN MENENGAH DI DESA BOJONG JENGKOL, KECAMATAN CIAMPEA, KABUPATEN BOGOR - Azizah Mursyidah; Hasbi Ash Shiddieqy; Muhammad Lutfi Tsamrotul Kholdi (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
The Covid-19 pandemic that occurred in Indonesia, precisely starting from 2020, had a very negative impact on all sectors, especially in the economic sector. The Indonesian economy is developing but with this pandemic the economic system has stagnated. Community Service Activities in addition to aiming at providing knowledge also provide opportunities for students to contribute in the community and even contribute to the state, one of which is Community Service activities carried out by students of the Sahid Islamic Institute of Bogor in Kampung Cikiray, Desa Bojong Jengkol, Kecamatan Ciampea, Bogor. This Kampung Ckiray is one of the many areas that have been negatively affected by this pandemic, such as losing their jobs, decreasing people's purchasing power and causing the economy in this village to not develop properly. With the community service program, the author contributes by holding a sharia financing work program in this Kampung Cikiray which is focused on UMKM. This is done nothing but to redevelop the UMKM business in Kampung Cikiray.